On Studies on Silesian Paremiography and Paremiology - Przymuszała, Lidia; Świtała-Trybek, Dorota (Literatura Ludowa. Journal of Folklore and Popular Culture, 2018)
The aim of the article is to present the current state of research on Silesian paremiography and paremiology. The first part provides an overview of collections of proverbs from various parts of Silesia from the mid-nineteenth century to modern times. The second part discusses theoretical studies dealing Silesian proverbs, which are explored in various contexts and from various research perspectives (literary studies, folklore, linguistics, language and culture, etc.).